PMO-062 Nutrition support infrastructure in the East of England—Anglia nutrition network (ANNET). (28th May 2012) - Woodward, J; Fellows, I; Cartwright, A
Abstract : Introduction: ANNet—the Anglia Nutrition Network—was established in 2011 to provide a forum for inter-professional communication, sharing good practice and innovations across the Anglian region in order to improve the quality and experience of all aspects of nutritional care. 17 secondary acute hospital trusts participate in the network which looks after a population of approximately six million. This survey reports on the nutrition team infrastructure within the network. Methods: ANNet was established with a formal constitution voted at the inaugural Annual General Meeting in September 2011. Among the first activities of ANNet was a description of the nutrition infrastructure in the region. This first "5 min survey" was disseminated among lead clinicians participating in the network in order to develop a snapshot of in hospital parenteral nutrition practice. Results: The response rate was 100% of the 17 Trusts participating in the network. 15/17 Trusts have a nutrition support team but of these three had no nutrition support nurse specialists and 4 had no allocated consultant time. 13 teams were led by a gastroenterologist, one by a nurse and one by a chemical pathologist. 7/15 teams see patients on parenteral nutrition twice or less each week, and 6/15 carry out daily ward rounds. 10/17 Trusts provide out of hours PH, but only five of these with vitamins and trace elements and 5/17 are able to compound from scratch. A snapshot revealed 88 patients on PN at the time of the survey (14/million), of which 72% were type I intestinal failure, 18% type II and 10% type III. The median number of patients receiving PN was four, with only three Trusts providing PN for more than five patients at the time of the survey—two with seven (one of which did not have a nutrition support team) and one Trust with 26, providing 30% of the region's PN. Conclusion: Compared to national figures, a higher proportion of Trusts in the region have a nutrition support team, although in many instances this is incompletely staffed. There are a relatively small number of patients receiving PN at any one time in any Trust, but a surprisingly high proportion of these have type II intestinal failure which are currently scattered around the region. ANNet is a useful resource for gathering information with a 100% response from participating Trusts in the network, covering approximately 10% of the UK population. A follow-up survey will focus on intestinal failure surgery. Competing interests: None declared.